Acute Inescapable Stress Rapidly Increases Synaptic Energy Metabolism in Prefrontal Cortex and Alters Working Memory Performance. (16th March 2019) - Musazzi, Laura; Sala, Nathalie; Tornese, Paolo; Gallivanone, Francesca; Belloli, Sara; Conte, Alessandra; Di Grigoli, Giuseppe; Chen, Fengua; Ikinci, Ayşe; Treccani, Giulia; Bazzini, Chiara; Castiglioni, Isabella; et al.
Abstract: Brain energy metabolism actively regulates synaptic transmission and activity. We have previously shown that acute footshock (FS)-stress induces fast and long-lasting functional and morphological changes at excitatory synapses in prefrontal cortex (PFC). Here, we asked whether FS-stress increased energy metabolism in PFC, and modified related cognitive functions. Using positron emission tomography (PET), we found that FS-stress induced a redistribution of glucose metabolism in the brain, with relative decrease of [ 18 F]FDG uptake in ventro-caudal regions and increase in dorso-rostral ones. Absolute [ 18 F]FDG uptake was inversely correlated with serum corticosterone. Increased specific hexokinase activity was also measured in purified PFC synaptosomes (but not in total extract) of FS-stressed rats, which positively correlated with 2-Deoxy [ 3 H] glucose uptake by synaptosomes. In line with increased synaptic energy demand, using an electron microscopy-based stereological approach, we found that acute stress induced a redistribution of mitochondria at excitatory synapses, together with an increase in their volume. The fast functional and metabolic activation of PFC induced by acute stress, was accompanied by rapid and sustained alterations of working memory performance in delayed response to T-maze test. Taken together, the present data suggest that acute stress increases energy consumption at PFC synaptic terminals and alters working memory.